Nuclear cell-free DNA on the loose: an early warning signal of ischemia–reperfusion injury in kidney transplantation - Strandberg, Gabriel; Trattner Evetovics, Rebecca; Martin, Myriam ; 0000-0003-1526-8678; Raihle, Carl; Slivca, Oleg; Alam, Shahnawaz; Segelmark, Mårten ; 0000-0002-1221-0772; Christensson, Anders; Nilsson, Bo; Paul, Clara; Blom, Anna ; 0000-0002-1348-1734; Biglarnia, Alireza ; 0009-0004-2293-0740 (Frontiers in Immunology, 2026)
Introduction: Cell-free DNA is an emerging marker of allograft injury, yet its role in the immediate phase of ischemia–reperfusion injury remains incompletely understood. Methods: In this prospective cohort of 127 kidney transplant recipients (86 deceased donors, 41 living donors), intraoperative plasma samples were collected systemically pre-implantation and from the allograft vein postreperfusion. Nuclear and mitochondrial cell-free DNA were quantified, alongside subset assessments of neutrophil extracellular trap markers and soluble C5b-9 as a marker of thromboinflammation. An in vitro necrosis model of human proximal tubular cells evaluated the concordance between cell injury and C5b-9 generation. Results: An immediate and sustained release of nuclear, but not mitochondrial, cell-free DNA was observed post-reperfusion, predominantly in deceased donor kidneys. This release corresponded with cold ischemic time and delayed graft function while showing temporal correlations with soluble C5b-9, indicating that cell-free DNA release parallels thromboinflammatory activation upon reperfusion. In vitro, C5b-9 generation occurred on necrotic, but not viable, tubular cells, supporting the relationship between cell injury and thromboinflammation. Neutrophil extracellular trap markers did not consistently correlate with early cell-free DNA release. Conclusion: Immediate nuclear cellfree DNA release upon reperfusion reflects intragraft injury linked to downstream thromboinflammatory activation, underscoring the impact of early ischemia–reperfusion injury.